Organocatalytic Phosphorylation of Alcohols Using Pyridine-N-oxide - Murray, James I.; Woscholski, Rudiger; Spivey, Alan C. (Synlett, 2015)
Phosphorylation of alcohols by phosphoryl chlorides catalysed by pyridine-N-oxide is reported. The utility of this method is demonstrated through phosphorylation of primary, secondary and a tertiary alcohol as well as phenols under mild reaction conditions and with low catalyst loading (5 mol%).
Keywords: phosphorylation; alcohols; pyridine-N-oxide; organocatalysis